Research on Mechanical Response of Pavement Structure to Differential Settlement of Subgrade on Highway Widening - Quanjun Shen; Yu Lu; Yaohui Yang; Guanxu Long (Advances in Materials Science and Engineering)
Based on the widening project of Ri-Lan highway in China, the finite element model is established by PLAXIS. By applying differential settlement at the bottom of the pavement, the mechanical response of the pavement structure is analysed. Finally, the differential settlement control standard indicated by crack strength is proposed. The results show that, under the effect of differential settlement, within about 4 cm of old pavement surface and upper base bear tensile stress, the base first reaches the failure strength. Under 4 cm of the old pavement surface, the subbase first reaches the failure strength. The differential settlement control standard of the pavement structure is determined by the splitting strength of the material, and we, respectively, control the differential settlement of less than 23.4 mm, where the corresponding cross-slope rate is 0.33%, and below 75.2 mm, where the corresponding cross-slope rate is 0.54%. It could support practical engineering applications.